Flow cytometric analysis of patients with hereditary spherocytosis – an Indian scenario. Issue 3 (16th March 2018) - Manivannan, Prabhu; Tyagi, Seema; Chandra, Dinesh; Mishra, Pravas; Pati, Hara Prasad; Saxena, Renu
ABSTRACT: Objectives: Flow cytometry osmotic fragility test (FC-OFT) was a recently introduced screening test for hereditary spherocytosis (HS). This study was conducted to evaluate the utility of FC-OFT in all newly diagnosed cases of HS, to compare its diagnostic value with conventional OFT and to correlate with clinical disease severity. Methods: In this study, the percentage of residual red cells (%RRC) was measured using flow cytometer after creating a red cell suspension. Subsequently, this was spiked with deionized water for FC-OFT in all cases of HS ( n  = 40), healthy subjects ( n  = 40) and beta-thalassemia traits (BTT) ( n  = 20). Results: The receiver operator curve analysis defined the optimal cut-offs for FC-OFT-derived indices, such as %RRC value (≤16.29%) and %RRC ratio (>1.72), for HS cases when compared with healthy subjects and BTT ( p  < 0.05). The FC-OFT (96%) achieved higher test efficiency than the conventional OF test (68.9%). A significant positive and a negative correlation were found between number of spherocytes/hpf and %RRC ratio ( p  = 0.001) and %RRC values ( p  = 0.0486). No significant correlation was observed between %RRC value ( p  = 0.8934), %RRC ratio ( p  = 0.6348) and HS disease severity score. Conclusion: Our results suggest that FC-OFT could be the better screening test for HS cases in developing countries if flow cytometer is available.